(untitled) (Research, Society and Development, 2023)
Blended teaching has brought about discussions about the inclusion of remote technologies in health education. Therefore, the objective of the article is to analyze the role of the hybrid modality of face-to-face and digital teaching in health education. The research methodology was carried out through an integrative literature review, using the following composite descriptor, which reflects the specificity of the investigated teaching modality: Hybrid Teaching in Health. The literature search took place between October 2021 and September 2022. Among the main results, a significant increase in the number of studies addressing hybrid health education as a topic is highlighted, expanding the discussion on the results of using the methodology, regarding its effectiveness in the learning process. It is concluded that the hybrid teaching modality in health plays a relevant role in the contemporary health education process. Despite the challenges, uncertainties, losses and damages, the pandemic has not been able to stop teaching. In this sense, there is a need to evaluate the long-term results of teaching and training in health in the hybrid modality.